Correlation between Maternal Hemoglobin Level and Birth Weight - Syifa Fauziyah Safithri; Nia Kania; Aly Diana (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Pregnant women are susceptible to have anemia, marked by hemoglobin level <11gr/dL. Maternal hemoglobin levels may influence the nutritional transfer, oxygenation, and uteroplacental circulation of the babies which may affect the infant’s birth weight. This study aimed to explore the correlation between hemoglobin level and birth weight in pregnant women in rural area in Bandung.Methods: This cross-sectional study was conducted from August to September 2014, recruiting all pregnant women registered in a hospital in a rural areas Bandung. Hemoglobin level was obtained from the medical records and analyzed to correlate with birth weight (Pearson correlation).Results: In total, there were 95 pregnant women included. The mean of maternal hemoglobin level was 11.6±1.2gr/dL and birth weight was 2.927±398gram. The proportion of maternal anemia and low birth weights were 30.5% and 15.8%, respectively. Pearson correlation test showed r=-0.093 and p=0.369 which was not significant.Conclusions: There was no correlation between maternal hemoglobin level and birth weight. Other factors for low maternal hemoglobin need to be further explored.